Consumers’ expected information search behavior for a pharmaceutical treatment - Liu, Yifei; Fincham, Jack E.; Sperry, Morgan L. (Frontiers in Pharmacology, 2025)
ObjectiveThe Comprehensive Model of Information Seeking (CMIS) integrates multiple factors influencing information seeking. This study was to identify factors impacting consumers’ expected information search behavior for a pharmaceutical treatment. By examining the predictive utility of these factors, the CMIS could be improved in the context of health information search.MethodsA telephone interview was administered to a random-digit-dialed sample of 2,186 adult residents in a southern U.S. state. Measurements included expected information search for a pharmaceutical treatment within the next 2 weeks, self-rated health (SRH), extraversion, and demographics. SRH was measured on a 4-point scale (Excellent-4, Poor-1), with higher scores indicating better subjective health. A logistic regression was conducted, in which the outcome variable was the expected information search for a pharmaceutical treatment, and covariates were SRH, extraversion, and demographics.ResultsA total of 505 individuals participated. On average, they were 57 years old, and 61% of them were female. Fourteen percent of them expected to seek information for a pharmaceutical treatment. The logistic regression was significant (p < 0.01). SRH was a significant negative predictor (p < 0.05) and gender (female) was a significant positive predictor for the expected information-seeking behavior (p < 0.05).ConclusionConsumers with lower SRH and women were more likely to perform expected information search for a pharmaceutical treatment. These findings have implications for both the modification of the CMIS and the provision of healthcare interventions.